Probabilistic Analysis of Isotropic Versus Anisotropic Spatial Variability of Soil in Design of Prefabricated Vertical Drains for Ground Improvement - Bari, Wasiul; Shahin, Mohamed; Nikraz, Hamid (Research Publishing, 2011)
The design of soil consolidation via prefabricated vertical drains (PVDs) has been traditionally carried out deterministically and thus can be misleading due to the ignorance of the uncertainty associated with the inherent spatial variation of soil properties. To treat such uncertainty, the use of reliability-based design (RBD) methods has been widely accepted in recent years for many geotechnical engineering problems. However, to date, little research has been done to consider soil spatial variability in soil consolidation by PVDs and more research is immensely needed.